PERUBAHAN ENTITAS PALESTINA OLEH PBB DAN EKSISTENSINYA SEBAGAI NEGARA PEMANTAU NON ANGGOTA - Windy Widya Utami; Arif Arif; Jelly Leviza (Journal of USU International Law, 2013)
ABSTRACT THE CHAGE OF PALESTINE’S ENTITY BY UNITED NATION AND ITS EXISTENCE AS A NON MEMBER OBSERVER STATE   Israel - Palestinian conflict began when the issuance of UN resolution dividing Palestine into two parts. Israel getting more land while the Palestinians got smaller parts. The conflict culminated when Israel established the State of Israel in 1948 in Palestine by the resolution. Ongoing conflict, not a civil society of both Palestinian and Israeli victims. Palestine is a country that was fighting for its independence. In goal it formed the Palestinian Liberation Movement ( PLO ) which is the official representative of the Palestinians in the international world. Monitors the status of Palestine as a non-member entity makes not having a strong juridical status in the eyes of international law when it attacked by other countries. Palestinians do not have the right to vote to apply protection to the United Nations Security Council ( UNSC abbreviated hereafter ) or prosecution by the International Criminal Court, unless the Palestinian states are willing to accept the obligations arising as a result of a peaceful settlement as stated in Article 35 of the UN Charter. Issues raised in this paper is how the basic law or the requirements for recognition of a state by the UN, how to change the status of Palestinian statehood from observer entity to non- member observer state, and how the existence of Palestine as a non-member observer state. The research method used in this thesis tends normative legal research includes a study of the principles of law, the synchronization level of the law, legal history, and comparative law. The research method used in this paper is normative legal research includes a study of the principles of law, the law of synchronization standards, legal history, and comparative law. The method used is normative research using normative juridical approach. The results of this study indicate a change in the entity State of Palestine by the UN Monitoring Non Member is a big step for the Palestinians to get justice in the International Court of Justice. And also its presence in the international community have been recognized by other countries.   Keywords : Entities , Palestine , UN.